PENGARUH HEALTH EDUCATION TERHADAP PENGETAHUAN DAN SIKAP KELUARGA PENDERITA TB PARU DI WILAYAH KERJA PUSKESMAS PETERONGAN KABUPATEN JOMBANG: PENGARUH HEALTH EDUCATION TERHADAP PENGETAHUAN DAN SIKAP KELUARGA PENDERITA TB PARU DI WILAYAH KERJA PUSKESMAS PETERONGAN KABUPATEN JOMBANG - Zakiyah, Dewi; Wijaya, Arif; Wahdi, Achmad (LPPM STIKes Bahrul Ulum Jombang, 2023)
TuberculosisPulmonary TB (pulmonary TB) is a deadly infectious disease throughout the world, especially in Indonesia, this pulmonary TB disease is caused by Mycobacterium Tuberculosis where pulmonary TB is transmitted through the air, saliva and sneezing. Pulmonary TB cases are increasing due to lack of knowledge and attitudes, this is because patients with pulmonary TB produce phlegm carelessly and do not cover their mouths when coughing.The purpose of this study was to determine the effect of Health Education on the knowledge and attitudes of families of pulmonary TB patients in the Work Area of ​​the Peterongan Health Center, Jombang Regency. The design in this study usespre Experimental with pre-test post-test design method.Consisting of 23 populations, a sample of 23 people, using a total sampling technique. The independent variable is Health Education and the dependent variable is knowledge and attitude,using analysta Wilcoxon Signe Ranks Test. Hasil uji statistik menunjukkan bahwa pengetahuan keluarga pasien TB paru setelah diberikan Pendidikan Kesehatanhampir seluruhnya 91,3% berjumlah 21 responden memiliki pengetahuan yang baikdenganp nilai =,000 atau <0,05dan terhadap sikap keluarga pasien TB paru setelah diberikan Pendidikan Kesehatan hasil yang diperolehhampir semuanya positif 87,0% berjumlah 20 respondenmemiliki sikap positif denganp nilai =, 000 atau <0,05.